Changes in knee biomechanics after a hip-abductor strengthening protocol for runners with patellofemoral pain syndrome - Ferber, R.; Kendall, K. D.; Farr, L. (Journal of Athletic Training, 2011)
Context: Very few authors have investigated the relationship between hip-abductor muscle strength and frontal-plane knee mechanics during running.